Protic Ionic Liquids as Cell-Disrupting Agents for the Recovery of Intracellular Carotenoids from Yeast Rhodotorula glutinis CCT-2186 - Mussagy, Cassamo U. [UNESP] (2019)
Rhodotorula glutinis (R. glutinis) yeasts are natural sources of intracellular carotenoids such as β-carotene, torularhodin, and torulene. Since these yeasts are constituted by a rigid cell-wall structure, the use of energy-saving and high-efficiency cell disruption procedures is critical for carotenoids recovery. A new technology using protic ionic liquids (PILs) was here evaluated as an alternative platform to permeabilize the R. glutinis cells and to improve the extraction of β-carotene, torularhodin, and torulene. The cell disruption ability of 12 highly concentrated aqueous solutions of ammonium-based PILs was determined, evaluating the influence of the relative ion hydrophobicity, solid-liquid ratio, water content, and temperature. Carotenoid extraction yields increased with the hydrophobicity of the PILs (i.e., increase of alkyl chain length of the anion or cation), temperature (from 25 to 65 °C), and PIL concentration (from 75 to 90% v/v). Additionally, to demonstrate the potential of PILs in carotenoids recovery, solvent recycling and carotenoids polishing were carried out using a three-phase partitioning system. The results demonstrate that the use of PILs as cell-disrupting agents can be a simple, efficient, sustainable, and feasible method to recover intracellular carotenoids from microbial biomass.